AMSUTRAN: A microwave transmittance code for satellite remote sensing. (April 2019) - Turner, Emma; Rayer, Peter; Saunders, Roger
Highlights: AMSUTRAN produces channel-averaged transmittances for RTTOV satellite coefficients. The core of AMSUTRAN is MPM (Liebe 1989) with modifications over the last 20 years. Oxygen lines are from Tretyakov (2005) and 35 ozone lines from HITRAN (2000). The 183.31 GHz water vapour line air-broadening parameters are from Payne (2008). Future developments will focus above 200 GHz, in preparation for the ICI instrument. Abstract: We present the microwave line-by-line model AMSUTRAN, which has been developed at the Met-Office (UK) for over 20 years as part of the EUMETSAT-funded Numerical Weather Prediction Satellite Application Facility (NWP SAF). It produces profiles of layer-to-space transmittances that are representative of the swath of a satellite channel, which are used to train coefficients for the fast radiative transfer model RTTOV (Radiative Transfer for TOVS). At its core are absorption routines based on the Millimeter-wave Propagation Model (MPM), with subsequent modifications to its structure and spectroscopy that have been implemented over time. The most significant of these are: adoption of the Curtis-Godson method of determining the most representative quantities for an atmospheric layer, the complete replacement of all oxygen line parameters, replacement of the air-broadened half-width parameters of the 22.235 and 183.31 GHz water vapour lines, the addition of 35 ozone lines from the HITRAN database, and modifications to the dry continua. The impact of each change is shown in terms of the change in Top Of Atmosphere (TOA) brightness temperature simulated for the 22 channels of the Advanced Technology Microwave Sounder (ATMS) satellite instrument. The biggest effect by far is seen in the method of determining layer quantities, with sensitivities up to many degrees kelvin. To date, developments have focused on the 0–200 GHz range as this is the spectral limit of the current microwave radiometers in-orbit, however, a new generation of instruments heralded by the forthcoming Ice Cloud Imager (ICI) planned for launch in 2022, raises the performance requirements of AMSUTRAN to sub-millimetre frequencies.